A LABORATORY MODEL OF SUBDUCTION ZONE ANISOTROPY - Buttles J.; Olson P. (My University, 1998)
Measurements of split seismic shear-waves near Pacific subduction zones show that fast polarization directions are primarily trench-parallel in the seaward-side mantle beneath a subducting slab and variable in the mantle wedge beneath back arc basins. It is generally accepted that the azimuth of the fast polarization direction defines the average orientation of the crystallographic a-axis in olivine. Here we use laboratory experiments to determine the orientation of the olivine a-axis in the upper mantle in the vicinity of a subducting slab. A laboratory analog for olivine a-axis motion during creep deformation is developed using small cylinders (whiskers) suspended in a viscous fluid. Subduction beneath a stationary overriding plate, variable dip angles and realistic rollback and down-dip plate kinematics are examined. Plate rollback produces strong plate-parallel whisker alignments for all dip angles examined. Alignment in the wedge occurs in three layers: a layer of dip-parallel alignment above the downgoing plate, a layer of subhorizontal alignment beneath the overriding plate, and a core of intermediate orientations. The amount of alignment beneath the overriding plate and the wedge core decreases with increasing dip angle. Our results indicate that olivine a-axis orientation in the seaward-side mantle is controlled by the amount of slab rollback, and that orientations in the mantle wedge depend upon slab dip angle.